Transgender adolescents and genital-alignment surgery: Is age restriction justified?. (June 2019) - Horowicz, Edmund
In the case of controversial interventions there is a need for clinical guidelines to be founded on 'expert opinion' and an evidence base, in order to minimise individual clinicians making subjective decisions influenced by bias or cultural norms. This paper considers international clinical guidelines that through recommendation effectively prohibit the provision of genital-alignment surgery for competent adolescents with gender dysphoria. I argue that although the rationale for this particular guideline is based on serious concerns, these need to be better understood to allow reconsideration of this unilateral prohibitive recommendation. I do not propose that genital-alignment surgery should be prima-facia provided for any adolescent with gender dysphoria. Instead I argue that by developing our understanding of the current concerns, we can allow guidelines to incorporate a margin of clinical discretion, to allow clinicians to provide genital-alignment surgery to some adolescents, where clinically appropriate. In facilitating this we can move towards establishing a solid evidence-base. The basis of this position is that clinical guidelines and medical practice should treat these young people with the same standards of evidence-based care as others who have less controversial conditions. Whilst this paper uses English law and UK professional regulation for context, many of the ethical, legal and professional issues highlighted are applicable to other jurisdictions.